Long-Run Growth and Recycling: A Material Balance Approach - Karen Pittel; Jean-Pierre Amigues; Thomas Kuhn (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
In this paper we analyze the implications of recycling for long-run economic development. In contrast to former approaches, we take explicit account of the circulation of matter in the economy. Building upon a Romer (1990) type growth model we consider virgin resources and recycled wastes as essential inputs to production. These material inputs either end up as waste after consumption or are bound in the capital stock - depending on the utilization of the produced output. As accumulating wastes can be recycled and again be employed in production, the waste stock serves as a source of valuable inputs in our model. We focus on the implications of recycling-related market failures and the integration of material balances on the dynamics of the economy. It is shown that, even in the absence of environmental policy, long-run development is sustainable. Yet, optimal environmental policy can serve as a means to raise growth.
Keywords: O41; Q01; Q3; Q53; 330; non-renewable resources; recycling; endogenous growth; sustainable development; exhaustible resources; Erschöpfbare Ressourcen; Kreislaufwirtschaft; Endogenes Wachstumsmodell; Nachhaltige Entwicklung